Об одном алгоритме отыскания решений системы линейных неравенств - Ненахов, Э.И. (Теорія оптимальних рішень, 2005)
An efficient algorithm for finding a solution to system of linear inequalities is proposed. It is based on the procedure of cutting a simplex by a plane and of embedding an obtained “semisimplex ” into a new simplex of minimal volume. The computational experiment results are provided.